Exploring multisensory programs as early literacy interventions: a scoping review - Solichah, Novia; Fardana, Nur Ainy (Institute of Advanced Engineering and Science, 2024)
It is essential for children in their early childhood to possess early literacy. Over the past decade, there has been relatively limited exploration of multisensory approaches to enhance literacy skills in early childhood. Consequently, this study aims to conduct a scoping review to identify and synthesize research supporting multisensory programs as an early literacy intervention for children. We conducted searches in seven databases that were published from 2012 to 2022, resulting in the inclusion of sixteen articles meeting the specified criteria. Our findings reveal several forms of multisensory programs that parents can carry out to improve early literacy skills: i) visual (e.g., drawing, interpreting the meaning of the words/sentences they read, playing with alphabet cards, reading words or sentences correctly, and reading labels on food and toy packaging); ii) auditory (e.g., singing, reading story books, mentioning letter sound symbols, spelling syllables, language activities, speeches, and storytelling); iii) kinesthetic (e.g., dividing words according to syllables in children using media strips, writing, clapping, marching, dancing, and drama); and iv) tactile (e.g., write the word with the index finger on the flannel/cloth). Most of the included studies employed experimental or quasi-experimental study designs. Thus, future studies are advised to incorporate randomized controlled trials.